A root-knot nematode effector manipulates the rhizosphere microbiome for establishing parasitism relationship with hosts - Liu, Rui; Chen, Mengfei; Liu, Boliang; Huang, Kaiwei; Mao, Zhenchuan; Li, Huixia; Zhao, Jianlong (Frontiers in Microbiology, 2023)
Introduction Root-knot nematode (RKN; Meloidogyne spp.) is one of the most infamous soilborne plant diseases, causing severe crop losses every year. Effector proteins secreted by RKNs play crucial roles during plant-nematode interaction. However, less is known about whether RKN effector proteins can impact the rhizosphere microbial environment. Methods In this study, we investigated the rhizosphere microbiome community of MiMIF-2 (a plant immunity-modulating effector) transgenic Arabidopsis thaliana with or without nematode infection using the Illumina high-throughput sequencing analysis. Results and discussion The results showed that the bacterial species richness index increased, while the fungi species richness index decreased in M. incognita-infected MiMIF-2 transgenic A. thaliana plants. The relative abundance of genera such as Clitopilus, Komagataeibacter, Lactobacillus, Prevotella, Moritella, Vibrio, Escherichia-Shigella, and Pseudomonas was reduced in MiMIF-2 transgenic A. thaliana plants compared to wild type, but was significantly increased after inoculation with M. incognita. The Cluster of Orthologous Genes (COG) function classification analysis revealed a decrease in the relative abundance of defense mechanisms, secondary metabolite biosynthesis, transport, and nematode infection catabolism-related functions in MiMIF-2 lines compared to the wild type. These differences may be the reason for the increased susceptibility of MiMIF-2 transgenic A. thaliana to nematode infection. Our results provide a new insight into RKN effector proteins and their association with the microbial community, host, and plant pathogens, which will lead to the exploration of new innovative ideas for future biological control of RKNs.